Literature Review : Investigasi Pengaruh Polutan Mikrologam, dan Mikroplastik terhadap Ekosistem Pesisir Pantai Bali - Muhammad Nuh Fathsyah Siregar; Agoes Soegianto (Jurnal Biologi dan Pembelajarannya (JB&P), 2024)
The island of Bali has become a popular tourist destination, but its impact on the coastal environment, particularly Serangan Beach in Bali is highly neglected. The method used in this research is a literature study of the distribution of microplastic and microplastic waste found on the coast of Serangan Beach Bali, through digital literacy journals such as Google Scholar, Science Mago and Science Direct. Based on some of these journals, it was found that micrometals pollutants, and microplastics that are not cleaned up can cause pollution of the flora and fauna ecosystem of Serangan Beach Bali. Although the impact of micrometals and microplastics in the present is not great, it will have a great impact in the future if there is no proper effort to overcome it.. This investigation is important to provide a better understanding of the impacts of micrometals and microplastic pollution on Bali's coastal ecosystems and to inform more effective environmental policies and management actions to protect and maintain marine resources critical to environmental sustainability and human well-being.